Exploration of Student Thinking Systems Through STEM-PjBL Project Based Learning in the Science Field - Sukarma, I Ketut; Hulyadi, Hulyadi; Muhali, Muhali; Azmi, Irham (Universitas Pendidikan Mandalika, 2024)
The complexity of science concepts which are interrelated with each other requires the competence to think systematically. Complex thinking which is the basis for critical, analytical, creative and metacognitive thinking is very important to master in responding to the challenges of the 21st century. The aim of this research is to explore students' thinking systems taught using the STEM-PjBL model. This research is quantitative descriptive research. The variables studied are students' thinking systems based on the ability to determine components that influence each other in the bioethanol synthesis and dehydrator processes. The population in the study was 17 students. Students are distributed in two semesters, namely semesters II and IV. The research uses pre-test and post-test systematic thinking ability tests as data collection techniques and tools. The test consists of 5 essay questions that assess students' systematic thinking competence, and the test used is analyzed for validity, discrimination power, and level of difficulty before use. This test was developed based on indicators of systematic thinking competency. Tests were given to students before and after carrying out project activities for making and dehydrating bioethanol. After carrying out the project, students strengthen their competence through computational simulations related to the project being carried out. The data obtained is then presented in a communicative graph. The research results showed that 35.2% had high system thinking, 29% medium, 35.6% low. These results show that the application of the STEM-PjBL model is able to foster students' systematic thinking competency.